Correlation between Particulate Matter 10 (PM10) Exposure Time and Black Dots in Buccal Cells of Medan Landfill Recycling Workers (Baghdad Science Journal, 2024)
This research explores the link between particulate matter (PM10) exposure and number of black dots in buccal epithelial cell nuclei in recycling workers (PDU), at the Medan City landfill, Indonesia. The study aims to identify the correlation PM10 levels, pollutant characteristics at the landfill, the appearance of AgNOR-expressed black dots in PDU groups. The measurements of PM10 exposure were carried out in open landfills in Medan city, and the subject of study is recycling workers who worked in landfills. Buccal epithelial cells were collected using an oral cytobrush smear, and the black dots were examined cytologically. Statistical analysis assessed the relationship between prolonged PM10 exposure and the number of black dots. The study found that most recycling workers were older than 55 (36%), with significant pollution exposure effects indicated by a higher average number of black dots in their buccal cells compared to non-recycling workers (BPDU), with the highest numbers in the 36-45 and 46-55 age groups (each 30%). When looking at their work hours, more than half of BPDU workers (52%) worked for 8 hours a day, and the majority of PDU also worked for the same duration of time. This suggests an association between their occupational exposure to environmental pollutants and health impacts, also considering age and work hours. The findings underscore the need to factor in these aspects when addressing worker health in polluted environments.